Penerapan Toleransi di Ranah Mahasiswa Teknik Lingkungan UPN â€œVeteranâ€ Jawa Timur Angkatan 2022 - Putri Aprillia Wijayanti; Mutiara Saniyyah Rochmasia; Seren Nurkhalisha (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Tolerance is an attitude of openness and mutual respect between individuals, groups and groups. In a tolerant life, equivalence in life takes priority. The application of tolerance that occurs a lot, one example in the scope of the campus. In this study, we have the goal of knowing the level of understanding and awareness of UPNVJT Environmental Engineering students Batch 2022 about the importance of tolerance in existing differences, what activities can be carried out as a forum for increasing tolerance in UPNVJT Environmental Engineering Students Batch 2022, and the benefits that can be obtained from the application of tolerance in differences among UPNVJT Environmental Engineering students Class of 2022, both in terms of personal development and academic learning. This research used a qualitative method by interviewing Environmental Engineering students at UPN